Predictors of discordance and concordance in reporting of intimate partner violence: Evidence from a large sample of rural Ethiopian couples - Leight, Jessica; Deyessa, Negussie; Sharma, Vandana (International Food Policy Research Institute, 2022)
Intimate partner violence (IPV) is a major worldwide health challenge, and addressing this challenge requires high-quality data. This analysis uses a large-scale survey of 5,033 households in rural Ethiopia in which both men and women were surveyed about past-year IPV in order to quantify the degree of discordance, including both husband only reporting and wife only reporting, for multiple forms of IPV (emotional, physical and sexual). In addition, logistic regression is employed to analyze the effects of demographic characteristics and individual norms and behaviors on the probability of discordant reporting. The results suggest that almost half of households (44%) are characterized by discordant reporting in at least one dimension of IPV. Given the high level of discordance, 61.4% of households report any physical and/or sexual IPV using the household-level measure, compared to a rate of 41.9% from the women’s data only. In addition, men who report more gender-equitable attitudes and behaviors (failing to concur with justifications for IPV, reporting higher support for gender equitable norms, and reporting a higher level of female engagement in decision-making and intrahousehold task-sharing) are more likely to be members of wife only reporting households: i.e., they are less likely to report perpetration of IPV. Women who report more gender-equitable attitudes and behaviors, by contrast, are more likely to be members of husband only reporting households.